2017
DOI: 10.1007/s10745-017-9954-x
|View full text |Cite|
|
Sign up to set email alerts
|

Hiding in the dark: Local ecological knowledge about slow loris in Sarawak sheds light on relationships between human populations and wild animals

Abstract: Local ecological knowledge (LEK) increases understanding of certain species and the threats they face, especially little-studied taxa for which data on distribution and conservation are often lacking. We conducted 111 semi-structured interviews in Sarawak, Malaysia, to collect local knowledge about the behavior and distribution of the Philippine slow loris (Nycticebus menagensis) from two ethnic groups, the Iban and the Penan. Our study revealed that male Penan respondents, generally hunters, who frequently go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Slow lorises are still heavily threatened due to habitat loss and illegal wildlife trade for food, pets and medicines (Shepherd et al, 2005;Nekaris and Starr, 2015;Miard et al, 2017), including in Laos, Cambodia and Thailand (Nekaris et al, 2010). Wildlife trade is the main factor determining the decline in slow loris population (Nekaris and Streicher, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Slow lorises are still heavily threatened due to habitat loss and illegal wildlife trade for food, pets and medicines (Shepherd et al, 2005;Nekaris and Starr, 2015;Miard et al, 2017), including in Laos, Cambodia and Thailand (Nekaris et al, 2010). Wildlife trade is the main factor determining the decline in slow loris population (Nekaris and Streicher, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Slow and pygmy lorises are imperiled due to a multitude of factors such as the illegal pet and photo prop trade, demand within traditional medicines and black magic, and direct consumption. Across a range of countries, such as India, Indonesia, Cambodia, Malaysia, and Vietnam, studies have revealed diverse sets of traditions, beliefs, myths, and taboos related to lorises that determine whether they are utilized as pets, hunted for food or medicine, or whether they are avoided entirely [17][18][19][20][21][22]. For instance, in some Sundanese communities of West Java, Indonesia, myths about slow loris (N. javanicus) blood causing all manner of phenomenon from the drying of soil and the dying of plants to landslides and the collapse of entire mountains seem to ensure that they are left alone [18].…”
Section: Introductionmentioning
confidence: 99%
“…LEK has been used to gather information on several elusive species, including the Hispaniolan solenodon (Solenodon paradoxus) and the Hispaniolan hutia (Plagiodontia aedium), allowing researchers to assess their status as well as threats [38]. LEK also helps to elucidate the threats that the species face and can help determine attitudes towards the animals of focus, even with ~40 informants [20,39,40]. In past studies, LEK has provided crucial conservation information for slow lorises in Java, Borneo, and Cambodia [18,20,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, included in Appendix I in the Convention on International Trade in Endangered Species (CITES) all international commercial trade in slow lorises is forbidden (Nekaris and Nijman, 2007). The trade of slow loris is a major threat to these species, where they are traded domestically and internationally for pets, traditional medicine, and meat consumption (Nekaris et al, 2013;Nekaris and Starr, 2015;Miard et al, 2017;Uprety et al, 2021). In addition to the conservation implications, the consumption of bushmeat from wild animals can pose a significant risk of zoonotic disease transmission and microbiological contamination, which could become a public health threat (Temmam et al, 2017).…”
mentioning
confidence: 99%